The Jiankang Empire in Chinese and world history - Chittick, Andrew ca. 20./21. Jh (Oxford studies in early empires, 2020)
This work offers a sweeping reassessment of the Jiankang Empire (third to sixth centuries CE), known as the Chinese "Southern Dynasties." It shows how, although one of the medieval world's largest empires, Jiankang has been rendered politically invisible by the standard narrative of Chinese nationalist history, and proposes a new framework and terminology for writing about medieval East Asia. The book pays particular attention to the problem of ethnic identification, rejecting the idea of "ethnic Chinese," and delineating several other, more useful ethnographic categories, using case studies in agriculture/foodways and vernacular languages. The most important, the Wuren of the lower Yangzi region, were believed to be inherently different from the peoples of the Central Plains, and the rest of the book addresses the extent of their ethnogenesis in the medieval era